(untitled) (Research, Society and Development, 2019)
The integrity of natural systems is already at risk because of climate change caused by the intense emissions of greenhouse gases in the atmosphere. The goal of geological carbon sequestration is to capture, transport and store CO2 in appropriate geological formations. In this review, we address the geological environments conducive to the application of CCS projects (Carbon Capture and Storage), the phases that make up these projects, and their associated investment and operating costs. Furthermore it is presented the calculations of the estimated financial profitability of different types of projects in Brazil. Using mathematical models, it can be concluded that the Roncador field presents higher gross revenue when the amount of extra oil that can be retrieved is 9.3% (US 48.55 billions approximately in 2018). Additional calculations show that the Paraná saline aquifer has the highest gross revenue (US 6.90 trillions in 2018) when compared to the Solimões (US 3.76 trillions approximately in 2018) and Santos saline aquifers (US 2.21 trillions approximately in 2018) if a CCS project were to be employed. Therefore, the proposed Carbon Capture and Storage method in this study is an important scientific contribution for reliable large-scale CO2 storage in Brazil.